Advocating Transitional Justice in Africa The Role of Civil Society (Springer Series in Transitional Justice, 2018)
This volume documents and analyses the strategies used by African civil society organisations to lobby for and enact transitional justice measures in their countries. The book offers local practitioners and African scholars space to reflect on the development and effectiveness of strategies in promoting transitional justice, as well as to identify the theoretical and contextual influences on transitional justice work. Most importantly, it presents lessons and best practices for advocating transitional justice. This edited volume fills a significant gap by providing an up-to-date regional African perspective on transitional justice in the form of a compilation of country-specific and thematic analyses of agenda-setting and lobbying efforts. It also offers insights into the state-civil society relationship on the continent. While including some historical perspective, the book chapters provide fresh and up-to-date insights into ongoing transitional justice efforts that are key to defining the future of how the field is understood in theory and in practice. .